KONSEP DESA DAUR ULANG SEBAGAI INISIASI MENCIPTAKAN KEWARGANEGARAAN EKOLOGI DIGITAL DI KABUPATEN JEMBER - Arka Widyadhana Putaraama; Muh. Zacky Daffa; M. Asif Nur Fauzi (YAYASAN PERCIKAN INSAN MANDIRI (PRISMA), 2025)
This study examines the role of Kampoeng Recycle in fostering ecological citizenship in the digital era. Addressing the environmental challenges posed by digitalization, such as increased consumerism and electronic waste, this initiative integrates community-based waste management with digital tools to enhance public participation. The research employs a qualitative approach through literature studies, analyzing the strategies of Kampoeng Recycle, including eco-structures, eco-literacy, and eco-preneurship. Key findings highlight the involvement of youth, the use of social media for networking, and the dissemination of ideas through digital platforms as pivotal in creating sustainable environments. The study concludes that Kampoeng Recycle significantly contributes to raising ecological awareness, though further research is needed to expand its application to broader communities.